From many one: Novel approaches to translation quality in a social network era - Jiménez-Crespo, Miguel A. (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
For decades, the fuzzy notion of translation quality has evolved parallel to the theorizations of translation and localization. This paper focuses on a novel approach to quality evaluation in the localization industry: how Facebook crowdsourced quality evaluation to an active community of users that votes on proposed translations. This approach, unthinkable a decade ago, seems to combine and distill some of the best aspects of several previous Translation Studies evaluation proposals, such as user-based approaches (Nida, 1964), functionalist approaches (Nord, 1997; Reiss and Vermeer, 1984) or corpus-assisted approaches (Bowker, 2001). These models were largely criticized at the time because they did not explicitly indicate how they could be professionally implemented. The current paper critically reviews the emerging crowdsourcing model in light of these approaches to quality evaluation and describes how mechanisms suggested in these earlier theoretical proposals are actually implemented in the Facebook model.